2020
DOI: 10.1038/s41598-020-62543-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic mycobacterial molecular patterns partially complete Freund’s adjuvant

Abstract: Complete Freund's adjuvant (CFA) has historically been one of the most useful tools of immunologists. Essentially comprised of dead mycobacteria and mineral oil, we asked ourselves what is special about the mycobacterial part of this adjuvant, and could it be recapitulated synthetically? Here, we demonstrate the essentiality of N-glycolylated peptidoglycan plus trehalose dimycolate (both unique in mycobacteria) for the complete adjuvant effect using knockouts and chemical complementation. A combination of synt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 47 publications
0
37
0
1
Order By: Relevance
“…Mycobacteria produce a distinct NOD2 ligand, N-glycolyl MDP, while most other bacteria produce N-acetyl MDP (84,85). N-glycolylated peptidoglycan and MDP were shown to be better inducers of immune responses compared to the N-acetylated forms by comparing with mycobacterial KOs and synthetic MDPs (86)(87)(88). The absence of NOD2 during Mtb infection was accompanied by reduced nitric oxide and cytokine production from mouse macrophages (89,90) and reduced iNOS from human macrophages (91).…”
Section: Nod-like Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacteria produce a distinct NOD2 ligand, N-glycolyl MDP, while most other bacteria produce N-acetyl MDP (84,85). N-glycolylated peptidoglycan and MDP were shown to be better inducers of immune responses compared to the N-acetylated forms by comparing with mycobacterial KOs and synthetic MDPs (86)(87)(88). The absence of NOD2 during Mtb infection was accompanied by reduced nitric oxide and cytokine production from mouse macrophages (89,90) and reduced iNOS from human macrophages (91).…”
Section: Nod-like Receptorsmentioning
confidence: 99%
“…NOD2 signalling has been called “non-redundant” in that although there are shared pathways with TLR and CLR signalling (e.g. NF-κB), NOD2 signalling appears to work synergistically with other MAMPs and little immune response is produced with MDP stimulation alone ( 86 , 88 , 92 ).…”
Section: Prrs and Their Functions Against Mtb At The Cellular Levelmentioning
confidence: 99%
“…Analysis of the in vitro LDH lysis activity of these three peptides ( Figure 3(c) ) showed that Rv1218c-p24 and the Rv2477c-p182-induced T cells lysed peptide-loaded T2A2 cells, so these two peptides were selected for an in vivo assay. Several studies have shown that complete Freund's adjuvant (CFA) significantly enhances the phagocytosis by macrophage in mice, and that this is closely associated with the improved immune response conferred by adjuvants [ 42 , 43 ]. In an in vivo experiment in mice, the CFA adjuvant was subcutaneously injected first into the mouse, then the antigenic peptide was subcutaneously emulsified with IFA.…”
Section: Discussionmentioning
confidence: 99%
“…The EESM was also tested against CFA (an oil suspension containing killed M. tuberculosis), an immunogenic/in ammatory stimulus since it is not possible to work with viable M. tuberculosis (Dubé et al, 2020). The CFA induced persistent edema, mechanical hyperalgesia and cold sensitivity in control animals for 22 days.…”
Section: Discussionmentioning
confidence: 99%